2016
DOI: 10.1159/000452513
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Diagnostic Accuracy of RTE and SWE in Differentiating Malignant Thyroid Nodules from Benign Ones: a Meta-Analysis

Abstract: Background: Approximately 10-20 million Americans have been clinically diagnosed with thyroid nodules. Shear wave elastography (SWE) and real-time elastography (RTE) are two primary forms of elastography for identifying the status of thyroid nodules. The aim of this study is to assess the performance of RTE and SWE in identifying malignant thyroid nodules. Methods: Relevant articles were systematically retrieved from PubMed, Embase and Cochrane Library. In order to evaluate the overall diagnostic accuracy, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 83 publications
1
19
2
1
Order By: Relevance
“…Studies included nodules from 2 -71 mm and most were papillary carcinomas. Therefore, cut-off values have a wide range and a single threshold cannot be established [82,83,85]. The sensitivity for SWE has been reported as 63.8 -93.8 %, and the specificity as 50 -88.2 % [96, 97, 100, 102, 104 -106].…”
Section: Swementioning
confidence: 99%
“…Studies included nodules from 2 -71 mm and most were papillary carcinomas. Therefore, cut-off values have a wide range and a single threshold cannot be established [82,83,85]. The sensitivity for SWE has been reported as 63.8 -93.8 %, and the specificity as 50 -88.2 % [96, 97, 100, 102, 104 -106].…”
Section: Swementioning
confidence: 99%
“…A big meta-analysis on 71 studies with a total of 16,624 patients showed that RTE is slightly better in differentiating benignancy from malignancy in thyroid lesions, with pooled Se = 82.9% for RTE; Se = 78.4% for SWE and Sp = 82.8% for RTE; and Sp = 82.4% for SWE [66].…”
Section: Rte Versus Swe Elastographymentioning
confidence: 99%
“…It is nowadays more and more widely used to better thyroid nodule discrimination. Both real-time elastography (RTE) and shear wave elastography (SWE) proved to have good results in indicating the malignancy risk using increased stiffness as a criterion of suspicion, with superior outcomes for RTE [8][9][10].…”
Section: Introductionmentioning
confidence: 99%